Strategi Bank dalam Meningkatkan Jumlah Nasabah pada Produk Pembiayaan KPR Ib Muamalat KCP Ponorogo - Ro Esta Wintari; Khoirun Nisak (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: The research in this thesis is motivated by the decline in the number of customers in the iB Muamalat KPR financing product, in this product the number of customers is the lowest compared to other products. Research Methods: This research method uses field research using a qualitative approach. Results: The results of this research are the bank's strategy in increasing the number of customers on the iB Muamalat KPR financing product, namely with an excellent service strategy which consists of 6 concepts, namely ability, attitude, appearance, attention, action, accountability. accountability. The supporting factors in increasing the number of customers are product quality, service quality and emotionality. Meanwhile, the inhibiting factors are that it is not easy to woo customers, frequent rejections, complaints about requirements, and competition with other banks. Conclusion: The bank's strategy has had a positive impact in increasing the number of customers.